2020
DOI: 10.1080/10717544.2020.1837295
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-deformable liposomes containing terpenes (terpesomes) loaded fenticonazole nitrate for treatment of vaginal candidiasis: Box-Behnken design optimization, comparative ex vivo and in vivo studies

Abstract: Fenticonazole nitrate (FTN) is a potent antifungal drug adopted in the treatment of vaginal candidiasis. It has inadequate aqueous solubility hence, novel ultra-deformable liposomes ‘Terpesomes’ (TPs) were developed that might prevail over FTN poor solubility besides TPs might abstain the obstacles of mucus invasion. TPs were assembled by thin-film hydration then optimized by Box Behnken design utilizing terpenes ratio (X 1 ), sodium deoxycholate amount (X 2 ), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 47 publications
(74 reference statements)
3
40
0
4
Order By: Relevance
“… 15 The particle size (PS) and the entrapment efficiency (EE%) were the selected CQAs that can significantly affect the quality and efficacy of the developed TPs. Based on literature review 16–19 and preliminary screening experiments (data is not shown), risk assessment was implemented to identify the process parameters that may potentially affect the CQAs of FTN-loaded TPs. In the current study, terpene type (X 1 ) and amount (X 2 ) were identified as the highest formulation risk factors affecting the CQAs of TPs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 The particle size (PS) and the entrapment efficiency (EE%) were the selected CQAs that can significantly affect the quality and efficacy of the developed TPs. Based on literature review 16–19 and preliminary screening experiments (data is not shown), risk assessment was implemented to identify the process parameters that may potentially affect the CQAs of FTN-loaded TPs. In the current study, terpene type (X 1 ) and amount (X 2 ) were identified as the highest formulation risk factors affecting the CQAs of TPs.…”
Section: Methodsmentioning
confidence: 99%
“… 11 The receptor medium was 50 mL of phosphate buffer saline solution (pH 7.4) containing 25% ethanol to maintain the sink condition. 16 Aliquots were removed at 1, 2, 3, 4, 5 and 6 hours. Samples were analyzed by UV spectrophotometer at λ max 252 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, FTN is thought to be a promising topical agent for treating skin fungal infections. Unfortunately, the low aqueous solubility of FTN (<0.10 mg/mL) (Albash et al., 2020 ) arouses the need for designing a new vesicular system to deliver FTN effectively and compel cure of fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental value of all prepared DC-BMs was applied into experimental design model and best fit model was found linear for vesicle size and 2nd order (2F1) model for EE. The adequate precision for VS and EE found >4 and represents model as well fitted [ 27 ]. The predicted R 2 values were found to be closer to adjusted R 2 and statistical analysis expressed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%